Successful Postoperative Nephrocutaneous Fistula Treatment With Omental Flap Grafting: A Case Report - Guan, Haonan; Zhang, Di; Ma, Xian; Lu, Yechen; Niu, Yiwen; Liu, Yingkai; Dong, Jiaoyun; Gao, Yi; Yang, Weiping; Chen, Qimin; Tang, Jiajun; Lu, Shuliang (Frontiers in Surgery, 2021)
Nephrocutaneous fistula (NCF) is a rare and severe complication of renal disease and surgical procedures. Treatments for NCF are based on the renal function, and can include nephrectomy, heminephrectomy, nephroureterectomy, endourological maneuvers or antibiotic therapy alone. Here we report a case of a chronic NCF which occurred 5 years after partial nephrectomy. In this report, we describe a new surgical approach for the management of a patient with postoperative NCF. In the present case, in addition to removing the fistulous tract, we also performed an omental flap grafting to tightly cover the kidney. In addition to limiting and controlling the local inflammation, the omental flap prevents contact between the kidney and the flank muscle on its posterior rim. No recurrence or complications occurred throughout 10 months of follow-up. The NCF was successfully treated with completely removal of the sinus tract and omental flap grafting, without nephrectomy. This case adds new aspects to the treatment of NCF.